Gender and geography in the United Kingdom, 1980-2006 - Jo Little (Documents d'Anàlisi Geogràfica)
This paper discusses the progress of feminist geography in the UK over the past 25 years. The first part of the paper refers to the earlier books and articles to establish key «moments» in the development of feminist geography in the UK; the second part goes on to document more recent developments in feminist geography such as the adoption of the concept of gender identity; the third section attempts to illustrate the main developments in feminist geography in the UK through reference to my own area of research, rural geography. Finally the paper briefly examines, by way of conclusion, the development of feminist geography in the UK in the context of teaching.